IMPLEMENTASI PENILAIAN AUTENTIK ASPEK SIKAP PADA PELAJARAN GEOGRAFI DI SMA NEGERI 1 SUNGAI PUAR - Nasri, Nadia; khairani, Khairani (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
This study aims to determine the implementation of Authentic Assessment of Attitude Aspects in Geography Lessons at SMA Negeri 1 Sungai Puar. This research is motivated by the existence of an authentic assessment which is considered the right assessment to measure the extent to which students' abilities and learning outcomes are. This type of research is a quantitative descriptive research. The population in this study was SMA Negeri 1 Sungai Puar with population characteristics, namely students of class X IPS T.P 2021/2022. The sampling technique used in this study was